ADEQUACY OF LOW-COST TECHNIQUE FOR SOIL BACTERIAL ALGINATE/ZEIN ENCAPSULATION AT LABORATORY SCALE - Álvaro Gutiérrez; Marcia Astorga-Elo; Daisy Tapia-Valdebenito; Claudia González Pastén; Carlos Peña-Farfal; Claudia Rabert; Irma Fuentes Lillo (Journal of the Chilean Chemical Society, 2023)
In the contemporary context, the utilization of microorganisms across various disciplines has emphasized the growing significance of comprehending their fundamental mechanisms and enhancing delivery techniques, particularly in agriculture. Microencapsulation is one notably viable technique that establishes a controlled microenvironment, thus safeguarding microorganisms, offering superior handling, stability, and precisely controlled release. To evaluate a low-cost technique adaptation, this study explores the encapsulation of one plant growth-promoting bacteria isolated from burned soil, utilizing the ion gelation method facilitated by a simplified syringe pump model. The core materials comprise sodium alginate and LB medium as the support matrix, complemented by zein as the protective coat. The best result for capsule formation with viable bacteria was obtained with a 5% sodium alginate matrix compound in 2.5% Luria Bertani broth and 5% Zein for coating.Additionally, in-depth insights into the chemical properties of the capsules and their components were obtained through ATR-FTIR spectroscopy, revealing vital interactions within these structures. In summary, this study represents a significant advancement in addressing contemporary agricultural challenges, especially those exacerbated by climate change. By introducing an economical and exploratory laboratory-scale technique for encapsulating soil bacteria, this research contributes to the development of sustainable agricultural practices. It underscores the potential of encapsulation in enhancing soil health, promoting plant vitality, and mitigating the adverse effects of climate change on agricultural ecosystems.